THE INFLUENCE OF DIGITAL MARKETING, OPEN HOUSE STRATEGY, AND THE AVAILABILITY OF HOUSING FACILITIES ON HOME PURCHASE DECISIONS AMONG EARLY MILLENNIALS IN SEMARANG - Alfikri, Naufal Daffa; Sudarsi, Sri (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the influence of digital marketing, open house strategy, and the availability of housing facilities on home purchase decisions among early millennials in Semarang City. A total of 207 respondents were selected using purposive sampling. Data were collected through an online Likert-scale questionnaire and analyzed using SPSS version 2022. The analytical methods included validity and reliability tests, multiple linear regression, as well as determination test, t-test and F-test. The findings show that all three independent variables have a significant and positive effect on purchase decisions. This study provides empirical evidence that digital marketing, direct experience through open houses, and adequate housing facilities play a crucial role in stimulating purchase interest among young buyers.